477OTepotinib plus gefitinib in patients with MET-amplified EGFR-mutant NSCLC: Long-term outcomes of the INSIGHT study. (24th November 2019) - Park, K; Zhou, J; Kim, D-W; Ahmad, A R; Soo, R A; Bruns, R; Straub, J; Johne, A; Scheele, J; Yang, J C-H; Wu, Y-L
Abstract: Background: In patients with EGFR-mutant NSCLC, MET amplification (METamp) is a resistance mechanism to EGFR tyrosine kinase inhibitors (TKI). In the randomized phase Ib/II INSIGHT study (NCT01982955) that halted full enrolment due to low recruitment, tepotinib (TEP), a potent, selective MET TKI, plus gefitinib (GEF) improved progression-free survival (PFS) and objective response rate (ORR) vs chemotherapy (CTx) in patients with EGFR-mutant NSCLC and resistance to 1 st -line EGFR TKIs due to METamp (≥6-month follow-up). We now present long-term survival outcomes (≥18-month follow-up) for this predefined analysis. Methods: Patients were randomized to TEP 500 mg + GEF 250 mg orally once daily (until progressive disease, intolerable toxicity or other withdrawal) or platinum + pemetrexed IV (≤6 x 21-day cycles). METamp was defined as GCN ≥5 and/or MET/CEP7 ratio ≥2. Primary endpoint was investigator-assessed (INV) PFS. Secondary endpoints included overall survival (OS), ORR, PFS by independent review (IRC), safety. Results: From 04/24/15 to 06/12/17, 55 patients enrolled in the INSIGHT study and 19 were METamp (TEP+GEF 12; CTx 7); this predefined subgroup is analysed here. Median GCN was 8.8 (range 4.8–29.5); 18 patients had GCN ≥5, 13 had MET/CEP7 ratio ≥2. At data cutoff (12/12/18), median treatment duration (weeks [range]) for TEP+GEF was 49 (4.6–110.9; 3 patients still ongoing for ≥24 months), pemetrexed was 18.0 (5.9–60.4), cisplatin 12.0 (6.6–25.1) or carboplatin 12.8 (5.9–19.7), all CTx patients discontinued. TEP+GEF compared with CTx improved PFS (INV mPFS 21.2 vs 4.2 months, HR [90% CI] 0.13 [0.04, 0.43]; IRC mPFS 19.3 vs 5.5 months; 0.18 [0.06, 0.61]) and OS (mOS 37.3 vs 13.1 months, 0.08 [0.01, 0.51]), as well as ORR (INV 66.7 v 42.9%; OR 2.67 [0.37, 19.56]; IRC 75.0 vs 42.9%; OR 4.00 [0.51, 31.38]). Grade ≥3 treatment-related AEs in METamp patients (≥15% in either arm, TEP+GEF vs CTx) were amylase or lipase increased (both 33.3% vs 0%), anemia, neutrophil or WBC count decreased (all 0 vs 28.6%). Conclusions: TEP+GEF improved survival of patients with EGFR TKI-resistant NSCLC due to METamp. TEP + osmertinib is currently being investigated in patients with METamp, EGFR-mutant NSCLC with acquired EGFR TKI resistance (NCT03940703). Clinical trial identification: NCT01982955. Editorial acknowledgement: Medical writing assistance was provided by Lisa Jolly, Bioscript, Macclesfield, UK, and funded by Merck KGaA, Darmstadt, Germany. Legal entity responsible for the study: Merck KGaA, Darmstadt, Germany. Funding: Merck KGaA, Darmstadt, Germany. Disclosure: K. Park: Advisory / Consultancy: AstraZeneca, Boehringer Ingelheim, Clovis; Elli Lilly; Hanmi; ONO; Roche; Novartis. R.A. Soo: Honoraria (self): BMS, Celgene, Ignyta, Lilly, Merck, Novartis, Pfizer, Roche, Taiho, Takeda, Yuhan; Honoraria (self), Research grant / Funding (institution): AstraZeneca; Honoraria (self), Research grant / Funding (institution): Boehringer Ingelheim. R. Bruns: Full / Part-time employment: Merck KGaA. J. Straub: Full / Part-time employment: Merck KGaA. A. Johne: Full / Part-time employment: Merck KGaA. J. Scheele: Full / Part-time employment: Merck KGaA. J.C-H. Yang: Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim, Eli Lilly, Bayer, Roche/Genentech/Chugai, MSD, Merck Serono, Pfizer, Novartis, Celgene, Merrimack, Yuhan Pharmaceuticals, BMS, Ono pharmaceutical, Daiichi Sankyo and AstraZeneca, Takeda Oncology, Blueprint Medicines, Hansoh Pharmaceu. Y-L. Wu: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Roche; Advisory / Consultancy, Research grant / Funding (institution): Boehringer Ingelheim ; Advisory / Consultancy: Merck; Honoraria (self): Eli Lilly, Pierre Fabre, Pfizer, Sanofi. All other authors have declared no conflicts of interest.